'Who did what for whom?' Amnesty International's Urgent Actions as activist-generated data. Issue 1 (1st January 2020) - Clark, Ann Marie; Zhao, Bi
Abstract: The historically growing awareness of human rights violations is attributable in large part to advocacy by nongovernmental human rights organizations (NGOs). Human rights advocacy techniques and the availability of information have not been constant, however. The use of NGO sources for information on human rights levels has implications for recent scholarly debates over information availability and human rights measurement. How have appeals on behalf of individuals changed as human rights concepts and legal standards have expanded? One way to get at this question is by taking advantage of event-based features of activist-generated data. We discuss the uses of such data with regard to a collection of documents on human rights advocacy for individuals, consisting of Amnesty International's Urgent Action bulletins on Latin America from 1975 to 2007. An illustrative case study focuses on changes in the use of legal standards in the human rights appeals addressing torture.